2000
DOI: 10.1577/1548-8659(2000)129<0962:rfacmf>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Regional Frameworks and Candidate Metrics for Assessing Biotic Integrity in Mid-Atlantic Highland Streams

Abstract: Regionally stratified biological criteria are being used increasingly to assess stream quality. We used multivariate analysis of variance and canonical analysis to examine the utility of two regional frameworks (basins and ecoregions) and 14 candidate metrics of local fish assemblages for assessing the biotic integrity of streams in the mid‐Atlantic highlands (montane areas from Pennsylvania to Virginia). In particular, we determined (1) how metrics varied naturally among basins and ecoregions and (2) which me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 30 publications
1
71
0
Order By: Relevance
“…We expected some metrics to be highly correlated because they contain similar composition, or they may have similar functional characteristics. When metrics were similar to each other (e.g., number of Trichoptera and percent of Trichoptera), we chose one based on a combination of lowest P-value from the t-test and lowest CV (ANGERMEIER et al, 2000;DAUWALTER et al, 2003).…”
Section: Metric Selectionmentioning
confidence: 99%
“…We expected some metrics to be highly correlated because they contain similar composition, or they may have similar functional characteristics. When metrics were similar to each other (e.g., number of Trichoptera and percent of Trichoptera), we chose one based on a combination of lowest P-value from the t-test and lowest CV (ANGERMEIER et al, 2000;DAUWALTER et al, 2003).…”
Section: Metric Selectionmentioning
confidence: 99%
“…For instance, the physiographic similarities along the boundary of the Mississippi and Atlantic drainages often produce ecologically similar (i.e., in ecological composition) riverine assemblages within the smaller streams draining either side of this boundary, as Angermeier and Winston (1998) and Angermeier et al (2000) found in Virginia (USA). However, from a taxonomic composition or phylogenetic standpoint, these ecologically similar assemblages are quite different as a result of their distinct evolutionary histories Winston 1998, Angermeier et al 2000).…”
Section: Hierarchical Classification Of Riverine Ecosystemsmentioning
confidence: 99%
“…Although multimetric indices are currently being developed and used to detect a broad array of human impacts to physical and chemical attributes of streams (Angermeier et al, 2000), the ability to separate or identify specific causes of impairment identified through the RBP process is limited. Even regionally modified or calibrated metrics provide little enhancement in the ability to identify or differentiate between causes of stream degradation such as point source or nonpoint source contamination (Schleiger, 2000).…”
Section: Discussionmentioning
confidence: 99%